Kobieta w domu i na rynku pracy. Czy równość praw i obowiązków? - Kwak, Anna (Wydawnictwo Naukowe UAM, 2007)
A woman is traditionally related to family roles. She is a wife, a mother, a housewife. Paid work is her additional role. Does the fact that she works professionally change the scope of her home responsibilities? Does she have a better position on work market because she has family obligations? The paper traces how reconciliation of family and professional duties is perceived and how it is realized in practice.
A woman in family and on the work market. Equality of rights and duties?